Evaluation of the haemocompatibility of TiO2 coatings obtained by anodic oxidation of Ti-6Al-4V - Vera, Maria Laura (2014)
The blood compatibility (haemocompatibility) is a requirement in materials used in prosthetic heart valves. No standardized methods are available to measure haemocompatibility in solid materials. However, a material could be considered haemocompatible if its surface does not modify the normal activation of the coagulation pathway and produces no damage in the blood components. In this work, the haemocompatibility of coatings obtained by anodic oxidation of Ti-6Al-4 V (with H2SO41 M and 40 to 70 V) with and without heat treatment (1 h for 500 °C), is evaluated and compared with the haemocompatibility of the Ti-6Al-4 V substrate and pyrolytic carbon. Standard clinical trials for clothing: Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) were adapted to evaluate the haemocompatibility of solid materials. Besides, the interaction between blood platelets and solid material were performed through an analysis of interfacial tension (γi,j), this parameter could indicate the degree of preferential adsorption of each protein of the blood plasma. The ratio between albumin-material and fibrinogen-material interfacial tension, (γs,Alb/ γs,Fib), is an important parameter used to predict the platelets adhesion and the trend at the formation of cloth. The results of the clothing trials indicate that the tested surfaces would be haemocompatibles due to the values of PT and APTT obtained which were in range of the normal ones. In addition, the measured values of γs,Alb/ γs,Fib indicate that all the tested surfaces are more haemocompatible than pyrolitic carbon. The recrystalized films by heat treatment which produce some rutile crystals are the most haemocompatibles.